The Challenges and Obstacles in Diagnosing Neuropathy in Patients With Diabetes - Sugianto; Monica Cindy Anjelica Novena Letsoin Pinzon; Rizaldy Taslim Pinzon Letsoin (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Background: Diabetes mellitus (DM) is a group of chronic metabolic diseases characterized by hyperglycemia. One of DM complication involve nerveous system disorder known as neuropathy. To prevent diabetic neuropathy developing into diabetic foot ulcer, early detection for the patient is necessary. However in implementing neuropathy screening tests, challenges and obstacles can be found. Objective: Assessing the challenges and obstacles in diagnosing neuropathy in patients with diabetes. Method: This study use a quantitative design with descriptive method. Data used in this study is secondary data with a total of 53 doctors as respondents. The data was then analyzed univariately using descriptive statistics to determine the frequency distribution. Results: In this study, only 9 respondents (17%) carried out neuropathy screening regularly. There are limitations to screening tools including tuning forks , neuropathy questionnaires, reflex hammers, monofilaments, and von Frey hair. Apart from that, the majority of respondents stated that they did not get enough time during the examination and the patients were not aware of their neuropathy condition. Conclusion: The results of this study show that there are challenges and obstacles in using neuropathy screening tests for neuropathy patients with diabetes mellitus.